The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1126/sciimmunol.aal5296
|View full text |Cite
|
Sign up to set email alerts
|

KIR2DS2 recognizes conserved peptides derived from viral helicases in the context of HLA-C

Abstract: This is the author accepted manuscript (AAM). The final published version (version of record) is available online via AAAS at http://immunology.sciencemag.org/content/2/15/eaal5296. Please refer to any applicable terms of use of the publisher. University of Bristol -Explore Bristol Research General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. KIR2DS2, an activating natural killer cell receptor recognizes highly co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
106
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(112 citation statements)
references
References 46 publications
4
106
1
Order By: Relevance
“…Romero et al found the interaction between KIR2DL3/2DL3 and HLA‐C1C1 associated with HCV spontaneous clearance ( p = 0.03, OR = 3.05) (Romero et al, ). Recently, Nalyer et al found KIR2DS2 recognizes conserved peptides derived from viral helicases in the context of HLA‐C, and KIR2DS2 in combination with HLA‐C1 was protective against chronic HCV infection ( p = 0.033, OR = 2.06, 95%CI: 1.06–4.02) in UK people (Naiyer et al, ). In present study, we did not find any associations between KIR2DL1, KIR2DL3, KIR2DS1 and their HLA‐C1 ligands.…”
Section: Discussionmentioning
confidence: 99%
“…Romero et al found the interaction between KIR2DL3/2DL3 and HLA‐C1C1 associated with HCV spontaneous clearance ( p = 0.03, OR = 3.05) (Romero et al, ). Recently, Nalyer et al found KIR2DS2 recognizes conserved peptides derived from viral helicases in the context of HLA‐C, and KIR2DS2 in combination with HLA‐C1 was protective against chronic HCV infection ( p = 0.033, OR = 2.06, 95%CI: 1.06–4.02) in UK people (Naiyer et al, ). In present study, we did not find any associations between KIR2DL1, KIR2DL3, KIR2DS1 and their HLA‐C1 ligands.…”
Section: Discussionmentioning
confidence: 99%
“…The activating KIR, KIR2DS2, is of particular interest given its protective role in bone marrow and cord blood transplantation for various hematological malignancies and in glioblastoma models in vivo . In addition, KIR2DS2 has recently been shown to directly recognise viral helicase peptides in the context of HLA‐C and to be protective against chronic hepatitis C virus infection . One of the barriers to understanding KIR2DS2 has been that, the high sequence homology between KIR2DS2 and the inhibitory KIR, KIR2DL2 and KIR2DL3, makes it difficult to develop antibodies that specifically detect KIR2DS2.…”
mentioning
confidence: 99%
“…The promiscuous nature of KIR2DL2 has been demonstrated through binding to a number of HLA‐C alleles while allelic diversity has also been shown to impact their specificity . While the ligands for activating KIR remain poorly characterised in general, KIR2DS1 has been demonstrated to mediate alloreactivity while KIRDS2 also appears to recognise discrete subsets of HLA class I allotypes . KIR3DS1 has been shown to reduce mortality and despite structural similarity to 3DL1 appears to recognise the non‐classical molecule HLA‐F .…”
Section: Discussionmentioning
confidence: 99%